Cost Implications of Varying the Surgical Setting and Anesthesia Type for Trigger Finger Release Surgery. Issue 5 (May 2019) - Kazmers, Nikolas H.; Stephens, Andrew R.; Presson, Angela P.; Yu, Ziji; Tyser, Andrew R.
Abstract : Background: Trigger finger release (TFR) is a common surgical procedure, representing a financial burden to the healthcare system. Our null hypothesis is that the choice surgical setting [operating room (OR) versus procedure room (PR)] and anesthetic type [local-only or monitored anesthesia care (MAC)] do not affect surgical encounter costs for TFR. Methods: Adult patients undergoing isolated unilateral TFR between May 2014 and December 2017 by 5 fellowship-trained hand surgeons at a single academic medical center were identified by Current Procedural Terminology (CPT) code (26055). We excluded patients undergoing revision surgery, tenosynovectomy, or additional procedures. Using our institution's information technology value tools, we calculated total direct costs for each surgical encounter, which were compared between groups. Univariate and multivariable gamma regression were used to model costs. Results: Of 210 included patients, 54% (113/210) of cases were performed in the PR and 46% (97/210) in the OR. No significant differences in demographics were observed between PR and OR groups. Compared to local-only in the PR, the OR with local-only, and OR with MAC, demonstrated 2.2- and 3.2-fold greater median costs. Multivariable models suggested that use of the OR independently led to 221% [95% Confidence interval: 137%–345%; P < 0.01] greater mean costs than the PR, and use of MAC was associated with 30% (95% confidence interval: 13%–49%; P < 0.01) greater mean costs for OR cases than local-only, while controlling for other confounders. Conclusion: Performing TFR in the PR setting under local-only anesthesia minimizes surgical encounter direct costs for this common procedure. Abstract : Supplemental Digital Content is available in the text.